Konseling Individu Dengan Teknik Self Management dalam Proses Rehabilitas Orang dengan HIV/AIDS (ODHA) - Dalinur M Nur; Lena Marianti; Adestari Aini (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2021)
The purpose of this study is to find out what causes the client "R" with HIV/AIDS to be disobedient in taking drugs and to find out how to apply individual counseling with Self Management techniques in the rehabilitation process of HIV/AIDS sufferers to the client "R". This research uses a qualitative case study method, namely research conducted in depth on the research subject (Client "R"). The object is a close friend and companion of the client "R". The location of this research is on Jalan Prameswara, alley of Macan Akar Bukit Baru, Palembang city. Data collection tools in the form of observation, interviews and documentation. The data analysis technique uses pattern matchmaking, explanation and time series analysis. The results of this study indicate that (1) the causes of non-compliance by client "R" in taking drugs are feeling lazy because they always have to take medicine, forgetting to take medicine when traveling, and finally the side effects of drugs that make client "R" play. (2) the results of the application of individual counseling with self-management techniques in the rehabilitation process of HIV/AIDS patients on client "R" which was carried out six times, showed changes in behavior as expected where initially client "R" did not comply with taking drugs indicated by behavior taking drugs not on time, not in appropriate doses and even not according to the doctor's rules and instructions, where after individual counseling with the Self Management technique the client "R" has shown increased compliance in taking drugs, it appears that he has taken drugs on time, following the doctor's instructions and rules.